OVERVIEW OF THE PUBLIC POLICIES IMPLEMENTED IN THE DELTA DO PARNAÍBA MARINE EXTRACTIVE RESERVE IN BRAZIL - Costa, Francisco Wendell Dias; Passos, Messias Modesto dos [UNESP] (Univ Federal Fluminense, 2023)
This study aims to provide an overview the implementation of public policies in the Delta do Parnaiba Marine Extractive Reserve (RESEX) located in the state of Maranhao in Brazil. This article is based on a descriptive qualitative approach and methodological procedures such as: bibliographical and documentary review and analysis, fieldwork, application of qualitative questionnaires, and photographic recording. Results have shown that the main public policies applied in the Parnaiba Delta RESEX include the Bolsa Verde Programme, the Credit and Installation Project of the National Rural Housing Programme (PNHR) and the Technical Assistance and Rural Extension Project. Additional measures and actions are included, among them the Royal Concession of Rights of Use (CCDRU) and Community-Based Tourism (CTB). Therefore, these implemented public policies have brought changes, especially in terms of the right to use the land, job creation, increase in income, and improvement housing. Said public policies must be committed and consistent to environmental management and land-use planning, ensuring the sustainability of natural resources, as well as protecting and recognising territoriality to guarantee the permanence of the population in the studied area.
Keywords: environmental management; sustainable use; public policy; Delta do Parnaiba